Physical activity and outdoor spaces before, during and after the COVID-19 Pandemic. PLAY LED Solution - Loureiro, Vânia (2021)
The coronavirus disease (COVID-19) pandemic has caused an exceptional lockdown, resulting in social isolation. In response this pandemic, many regions closed or restricted access to outdoor spaces such as municipal or public parks, community gardens, playgrounds, and many others. This results in a decrease of physical activity in the communities and in an increasing of the sedentary behaviours. Physical inactivity is one of the main risk factors for the development of chronic non-communicable diseases [1]. It is also reported the major active people prefer outdoor spaces for the practice of physical exercise. The PLAY LED solution is an interactive outdoor game, accessible for all generations, users of green and outdoor spaces resulting in a diversified, systematized and quality opportunity for physical activity. By applying game design elements and game principles in a non-game context, PLAY LED has developed an experience that leads sedentary people to get a physical activity opportunity, promoting active lifestyles in the community and also brain stimulation. The PLAY LED offer examples of strategies that may be implemented to reduce potential risks of COVID-19 transmission, challenging the modification of outdoor spaces to promote physical distancing; incite the use of all parks space; based on visual cues and restrict occupant capacity. On other and in order to help policymakers take new services and initiatives for the 21st century, PLAY LED could influence the behaviour and promote active lifestyles in society. It is a technological and innovative tool developed through interactive LED systems in which one of the main attractions is the fact that it is designed considering digital tools.